Predictive value of Computed Tomography Coronary Angiography for the evaluation of acute chest pain: single center preliminary experience - Maffei, E.; Palombo, A.; Martini et al., C. (Acta Biomedica Atenei Parmensis, 2011)
Aim: To assess the predictive value of CT coronary angiography (CT-CA) in the stratification of patients with acute chest pain. Materials and methods: We enrolled 48 patients (31 males and 17 females, mean age 61.0±14yrs) with acute chest pain of suspected coronary origin, without diagnostic alterations of the ECG and/or increase of the myocardial biomarkers. Sixty-four slice CT-CA was performed within 48-72 hours. Depending on the clinical judgment, the patients were dismissed or underwent conventional coronary angiography (CAG). Patients underwent clinical follow-up at 6 months, recording the prevalence of major cardiovascular events. Results: One patient was excluded from the analysis because of poor image quality. CT-CA showed no coronary artery disease in 38.3% (18/47) of the patients, no significant coronary artery disease (